The Influence of Greek Spirituality on Russian Culture - Ján Zozuľak (Religions, 2021)
In this article, we will analyze the influence of Greek spirituality on Russian culture in the second half of the 18th century, when Enlightenment ideas infused Russian society. Russian intellectual circles and the upper social class were inspired by Western categories of thought. The absence of a living theology that would give man the true meaning of life has caused tension and a great spiritual crisis in Russian society. One possible solution was to start a fight against the Enlightenment and reject any Western ideas. The second solution was to pay attention to the forgotten tradition and look for inspiration in it for the renewal of spiritual life. The spiritual renewal, known as the philokalic movement, leaned towards the second solution, building upon the Byzantine hesychastic tradition of the 14th century. This paved the way for a new era of Orthodox spirituality, which significantly influenced thinking and spiritual life in Russia. The movement of spiritual renewal is associated with the translation and publication of manuscripts written by Byzantine niptic authors, which were published in the book Dobrotolublye (gr. Philokalia). This significantly contributed to the spread of the hesychastic tradition in Russia and became an impetus for a return to Byzantine spiritual values. This article examines the spiritual, literary, and cultural activities of the most important centers of Russian Hesychasm, such as Sarov, Valaam, and Optina, and their influence on Russian society, which has not yet been recognized sufficiently.